FXIII-A Leu34 genetic variant in premature coronary artery disease: A genotype – phenotype case control study - Silvain, Johanne; Pena, Ana; Vignalou, Jean-Baptiste; Hulot, Jean-Sébastien; Galier, Sophie; Cayla, Guillaume; Bellemain-Appaix, Anne; Barthélémy, Olivier; Beygui, Farzin; Bal-dit-Sollier, Claire; Drouet, Ludovic; Weisel, John W.; Montalescot, Gilles; Collet, Jean-Phillippe (Thrombosis and Haemostasis, 2011)
The FXIII-A Leu34 genetic variant increases and accelerates fibrin stabilisation; however, its association with premature coronary artery disease (CAD) and thrombotic events remains controversial. FXIII Val34Leu genotype was determined in 242 young individuals (<45 years old) who survived a myocardial infarction (MI) and 242 healthy controls matched for age and gender. We evaluated its effect on longterm clinical outcome defined as a composite of cardiovascular death, recurrent MI and urgent revascularisation. In addition, fibrin clot stiffness (elastic modulus or EM) and response to rt-PA-mediated fibrinolysis (fibrinolysis rate) were measured ex vivo using the Hemodyne analyser and confocal microscopy as surrogate endpoint. FXIII-A Leu34 genetic variant was not associated with premature CAD (adj. odds ratio 0.83 [0.49–1.4]) nor did it influence clinical outcome in patients, during a median follow-up of 6.3 (± 2.4) years. Patients produced stiffer fibrin clots (median [IQR] EM =20.3 [14.9–28.1] vs. 12.8 [9.6–17.1] kdynes/ cm2; p<0.0001) and displayed reduced response to fibrinolysis with lower fibrinolysis rate (6.7 [3.4–11.0] vs. 9.0 [5.0–16.7] sec-1x10−4; p<0.0001) than healthy controls. Carriage of factor XIII-A Leu34 led to a stepwise decrease in fibrinolysis rate with a significant gene–dose-effect in patients (7.7 [4.1–12.2] vs. 4.8 [3.0–8.5] vs. 4.3 [2.4–8.1] sec-1x10−4, for wild-type, heterozygous and homozygous, p for trend =0.003) and a non-significant trend in controls (p=0.01). In conclusion, FXIII-A Leu34 is a polymorphism which provides a strong resistance to fibrinolysis with a gene-dose effect, but does not relate to premature CAD or to recurrent coronary events in this study.
Keywords: Factor XIII Val34Leu; pharmacogenetic; fibrinolysis; thrombosis; coronary disease; fibrin structure